Enhancing faculty professional development : a quest to empower lecturers in collaborative active learning - Chang-Tik, Chan (Emerald Publishing Limited, 2025)
In today's active learning scenario, the focus is on student learning and less on teaching. Enhancing Faculty Professional Development: A Quest to Empower Lecturers in Collaborative Active Learning provides tips and advice to empower lecturers in collaborative active learning through faculty professional development. The book is written for professional development (PD) practitioners and faculty developers as primary audience, it will also appeal to teacher educators, deans, education academy directors, lecturers, and students. Building on a user-friendly approach of faculty professional development, the book offers evidence-based insights from research findings. Drawing from the author's rich experiences as a professional development facilitator, Enhancing Faculty Professional Development offers practical tips for reshaping assessment and feedback practices, and design of learning activities aided by technologies including artificial intelligence. It recognises the importance of social media and digital technologies to support engagement and interaction in formal and informal learning spaces. This thought-provoking book provides practical strategies for incorporating collaborative active learning into teaching, while exploring the potential of faculty professional development to transform traditional teaching practices. This allows readers to discover how faculty professional development can help with the adoption of student-centred approaches and address personal and professional changes. Each chapter introduces a basic concept of collaborative active learning, explains the connections between research findings and their practicalities in real-world learning and teaching settings, and provides firm examples of how the interventions could be used in a variety of disciplines. Specially designed blended learning workshops in each chapter allow participants to collaboratively engage in purposeful critical discourse and reflection over the depth and breadth of the training content of their own unique needs. Readers are encouraged and supported to unlock the full potential of collaborative active learning and embrace its transformative power to take their professional careers to the next level.
Includes index.
Keywords: Active learning.; Teachers -- Training of.; Career development.; Education -- Philosophy, Theory & Social Aspects.; Play-based learning.; Philosophy and theory of education.; elektronické knihy; electronic books